Treatment and energy valorisation of an agro-industrial effluent in upflow anaerobic sludge reactor (UASB) - Martins, Ramiro (2020)
The accelerated growth of the population brings with it an increase in the generation of agro-industrial effluents. The inadequate discharge of these effluents significantly affects the quality of water resources. In this way, it becomes important to invest in treatment processes for agro-industrial effluents, particularly low-cost ones. In this context, the present study includes the design and construction of a UASB reactor and optimization of the anaerobic digestion treatment of the raw effluent from chestnut production in the agro-industrial company Sortegel. The efficiency of the system was evaluated through the determination / monitoring of Chemical Oxygen Demand (COD), Biochemical Oxygen Demand (BOD5), Total Suspended Solids (TSS), biogas production rate and quality (% methane). The reactor was fed for 25 weeks and operated under mesophilic conditions (temperature 30-40°C). Different values were tested for the hydraulic retention time (HRT) and volumetric flow rate (QV): 0.66 days (QV=1509 L.m-3.d-1); 1.33 days (QV=755 L.m-3.d-1); 2.41 d days (QV=415 L.m-3.d-1). The average COD removal efficiency reached values of 69%, 82% and 75%, respectively, and simultaneously the associated CBO5 removal efficiency was 84%, 91% and 70%. As regards TSS, removal values were 78%, 94% and 63%. In addition, high methane production rates were obtained, between 2500 and 4800 L CH4.kg-1 COD removed.d-1. For all the hydraulic retention times tested, high concentrations of methane in the biogas were recorded: 66-75%, 70% and 75% for HRT of 0.66, 1.33 and 2.41 days, respectively.